Writing science : literacy and discursive power - Halliday, M. A. K. (Michael Alexander Kirkwood), 1925-2018 (Critical perspectives on literacy and education., 1993)
This book is about the use of language in the science classroom. It discusses the evolution of scientific discourse for learning in secondary schools, and examines the form and function of language across a variety of levels including lexiogrammar, discourse semantics, register, genre and ideology. Special attention is paid to how this knowledge is imparted. It will be of particular interest to educators involved with linguistics and/or science curriculum and teachers of English for special and academic purposes.; It is aimed at teachers of undergraduates in science and literacy, linguists tea.